2014
DOI: 10.1371/journal.pone.0094249
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Optimization and Verification of Illumina-Generated 16S rRNA Gene Amplicon Surveys

Abstract: The exploration of microbial communities by sequencing 16S rRNA genes has expanded with low-cost, high-throughput sequencing instruments. Illumina-based 16S rRNA gene sequencing has recently gained popularity over 454 pyrosequencing due to its lower costs, higher accuracy and greater throughput. Although recent reports suggest that Illumina and 454 pyrosequencing provide similar beta diversity measures, it remains to be demonstrated that pre-existing 454 pyrosequencing workflows can transfer directly from 454 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
251
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(267 citation statements)
references
References 41 publications
(52 reference statements)
13
251
1
2
Order By: Relevance
“…The V4-V5 region of the 16S rRNA gene was amplified with forward primer 518F (5 -xx-CCAGCAGCYGCGGTAAN-3 ), and an 8 : 1 : 1 mix of the reverse primers 926R1 (5 -yy-CCGTCAATTCNTTTRAGT-3 ), R2 (5 -yy-CCGTCAATTTCTTTGAGT-3 ), and R3 (5 -yy-CCGTCTATTCCTTTGANT-3 ) (Nelson et al, 2014). Primers included 33 base pair (bp) adapters (xx, yy) at the 5 end.…”
Section: Nucleic Acid Extraction and Sequencingmentioning
confidence: 99%
“…The V4-V5 region of the 16S rRNA gene was amplified with forward primer 518F (5 -xx-CCAGCAGCYGCGGTAAN-3 ), and an 8 : 1 : 1 mix of the reverse primers 926R1 (5 -yy-CCGTCAATTCNTTTRAGT-3 ), R2 (5 -yy-CCGTCAATTTCTTTGAGT-3 ), and R3 (5 -yy-CCGTCTATTCCTTTGANT-3 ) (Nelson et al, 2014). Primers included 33 base pair (bp) adapters (xx, yy) at the 5 end.…”
Section: Nucleic Acid Extraction and Sequencingmentioning
confidence: 99%
“…In fact, with the very high coverage and relatively low complexity in this study, a rarely mentioned problem of "leakage" 435 between libraries was observed. This is also referred to as index misassignment and may interfere with high sensitivity amplicon sequencing approaches (Nelson et al, 2014). Some OTUs, very abundant in only one library (e.g.…”
mentioning
confidence: 99%
“…An obvious example was the leakage of 1-3 reads from the single marine library into the freshwater libraries and we used this to set the level of the threshold (0.1%) for 440 accepting the presence of an OTU in a library. Such technical artifacts during the MiSeq run are often not accounted for and may result from sequencing and image analysis errors during the index sequencing phase of the run (Nelson et al, 2014). Carry-over of amplicons from previous runs was not possible as the two runs (first containing the cormorant library and second containing all other libraries) with the myxosporean barcodes and primers were run several months apart.…”
mentioning
confidence: 99%
“…This problem, resulting from sequencing and/or image analysis errors during the index sequencing phase of the MiSeq run (a separate step in the sequencing process), causes a small fraction of amplicons from one library to be incorrectly assigned to an index of another library (Nelson et al, 2014). In the mock community analysis we clearly showed the relevance of this problem by identification of 2-7 OTUs that were contaminants from DNA extraction kits and cross-talk.…”
Section: Discussionmentioning
confidence: 92%
“…We strongly recommend the use of this procedure because our analysis showed that the contamination rate can be more than 2% in a MiSeq run. Within-run cross-talk can artificially inflate OTU numbers and diversity measurements if not properly addressed, leading to incorrect interpretation of results when investigating low abundance OTUs (Nelson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%